INFLUENCE OF SLOW AND RAPID COOLING ON THE STRUCTURAL STATE OF RHODIUM-DIFFUSED n-Si MONOCRYSTALS (International Conference on Education, Psychology and Humanities, 2026)
This thesis investigates the influence of slow and rapid cooling regimes on the structural state of rhodium-diffused phosphorus-doped n-type silicon monocrystals. Rhodium diffusion was carried out after high-temperature treatment at 1300 °C, and the structural changes were analyzed using X-ray diffraction with special attention to the dominant (111)Si reflection. The XRD profiles show that both slow-cooled and rapidly cooled n-Si samples preserve the main monocrystalline orientation of the silicon matrix. However, the cooling regime significantly affects the intensity and shape of the (111)Si diffraction peak. The slow-cooled sample exhibits a higher peak intensity and a broader diffraction line with FWHM = 0.163°, indicating stronger coherent scattering from the silicon matrix and a more developed redistribution of rhodium-related defect complexes. In contrast, the rapidly cooled sample shows a lower peak intensity and FWHM = 0.147°, which may be associated with the preservation of non-equilibrium defects, frozen microstrain fields, and local impurity-defect configurations. The observed difference between the two diffraction profiles confirms that post-diffusion cooling is an important technological parameter for controlling the structural state of rhodium-doped silicon. Slow cooling promotes partial relaxation and stabilization of Rh-related structural regions, whereas rapid cooling preserves a more non-equilibrium defect state.
Keywords: rhodium-diffused silicon, n-Si, slow cooling, rapid cooling, X-ray diffraction, (111)Si reflection, FWHM, microstrain, defect complexes.